2015
DOI: 10.4148/1051-0834.1056
|View full text |Cite
|
Sign up to set email alerts
|

A Review and Evaluation of Prominent Theories of Writing

Abstract: Theoretical frameworks bring order to phenomena and provide a context for both research and practice. However, it has only been in the last four decades that theoretical frameworks have guided writing research. Before the 1980s, writing research focused more on mechanics and grammar than on cognitive thought processes related to writing. During the mid-1990s, theories shifted to a more sociocultural view of writing. Therefore, the purpose of this study was to apply theory evaluation criteria to theories of wri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Writing instruction and research transitioned from grammar and mechanics in the pre-1970s era (Foster, 1983;Nystrand, 2006;Rose, 1985) to cognitive ability in the 1960s and 1970s and then to social concepts in the late 1980s and 1990s (Leggette, Rutherford, Dunsford, & Costello, 2015b;Nystrand). Early research agendas shifted the lines of inquiry from understanding writing to writing issues, evidence, audience, conclusion, principles, and discourse (Nystrand).…”
Section: Introductionmentioning
confidence: 99%
“…Writing instruction and research transitioned from grammar and mechanics in the pre-1970s era (Foster, 1983;Nystrand, 2006;Rose, 1985) to cognitive ability in the 1960s and 1970s and then to social concepts in the late 1980s and 1990s (Leggette, Rutherford, Dunsford, & Costello, 2015b;Nystrand). Early research agendas shifted the lines of inquiry from understanding writing to writing issues, evidence, audience, conclusion, principles, and discourse (Nystrand).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, researchers have developed several theoretical and conceptual frameworks related to writing and have shifted from a focus on mechanical errors and basic composition to a broader investigation of the various contexts in which writing is situated, including the cognitive processes and social and cultural influences involved (Prior, 2006). As a result, writing research has become more holistic and encompasses the conditions in which writing occurs rather than concentrating on a writer's ability to compose good text (Leggette, Rutherford, Dunsford & Costello, 2015).…”
Section: Review Of Literaturementioning
confidence: 99%
“…This dependence on other fields of interest has resulted in a community of scholarship lacking focus, rigor, and an integrated theoretical foundation. Additionally, because popular theories used within the agricultural communications discipline, such as uses and gratifications theory and gatekeeping theory (Evans, 2006), are not oriented within the writing research paradigm, few research studies consider the theoretical underpinnings of writing development or inform the profession how to teach writing (Leggette, Rutherford, et al, 2015). Furthermore, in a quantitative content analysis of the theories and models used in agricultural communications research, Baker and King (2016) concluded that a majority of studies rarely test or build upon existing theories.…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations